2015
DOI: 10.1021/tx500433r
|View full text |Cite
|
Sign up to set email alerts
|

Tributyltin Engages Multiple Nuclear Receptor Pathways and Suppresses Osteogenesis in Bone Marrow Multipotent Stromal Cells

Abstract: Organotins are members of the environmental obesogen class of contaminants because they activate peroxisome proliferator-activated receptor γ (PPARγ), the essential regulator of adipogenesis. Exposure to thiazolidinediones, PPARγ ligands used to treat type 2 diabetes, is associated with increased fractures. Diminished bone quality likely results from PPARγ’s role in promoting adipogenesis while suppressing osteogenesis of bone marrow multipotent mesenchymal stromal cells (BM-MSC). We hypothesized that tributyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 67 publications
3
46
0
Order By: Relevance
“…The organotin tributyltin (TBT), which inspired the coining of the term environmental obesogen, is an environmental PPARγ ligand (Grün et al 2006; Kanayama et al 2005). TBT is a highly potent PPARγ ligand, which induces differentiation of bone marrow and adipose-derived multipotent stromal cells (MSCs) into adipocytes and suppresses bone formation (Baker et al 2015; Grün et al 2006; Li et al 2011; Watt and Schlezinger 2015; Yanik et al 2011). Prenatal TBT exposure in mice leads to epigenetic changes in mesenchymal stem cells that favor adipogenesis at the expense of osteogenesis (Chamorro-García et al 2013), reduced ossification of the skeleton (Tsukamoto et al 2004), and increased adiposity in adulthood (Grün et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The organotin tributyltin (TBT), which inspired the coining of the term environmental obesogen, is an environmental PPARγ ligand (Grün et al 2006; Kanayama et al 2005). TBT is a highly potent PPARγ ligand, which induces differentiation of bone marrow and adipose-derived multipotent stromal cells (MSCs) into adipocytes and suppresses bone formation (Baker et al 2015; Grün et al 2006; Li et al 2011; Watt and Schlezinger 2015; Yanik et al 2011). Prenatal TBT exposure in mice leads to epigenetic changes in mesenchymal stem cells that favor adipogenesis at the expense of osteogenesis (Chamorro-García et al 2013), reduced ossification of the skeleton (Tsukamoto et al 2004), and increased adiposity in adulthood (Grün et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Baker et al 2015). To determine the potential nuclear receptor pathways235 involved, BM-MSC cultures were stimulated to undergo osteogenic differentiation and treated236 with Vh or TBT (80 nM).…”
mentioning
confidence: 99%
“…Organotins include tributyltin (TBT) and triphenyltin, substances with strong antibacterial and fungicidal properties that were historically used as marine anti-fouling additives in paint. Baker et al[38] showed that in BM-MSCs, TBT activated adipogenesis and reduced osteogenesis. This finding was also supported in primary BM-MSCs for both TBT and tryphenyltin[39].…”
Section: Heavy Metalsmentioning
confidence: 99%